Aplicação de sais hidrossolúveis para tratamento de madeira roliça por meio de métodos não industriais - Ravasi, Roger (2015)
Wood is an organic material which may decompose or deteriorate. To avoid this, the wood needs to go through preservative treatments, ensuring a higher durability to the treated pieces. This research aimed to evaluate the efficiency of methods that combine sap substitution treatment and distribution in Eucalyptus grandis, using a mixture of preservative substances copper base, chromium and boron. The material was collected in 10 years old existing heterogeneous plantations at the Federal University of Santa Maria. After conducting an inventory in the population, there were taken randomly, 2 trees per treatment, and each tree removed 3 pieces measuring 2 meters each. There were felled 12 trees to perform 6 treatments. The methods used were diffusion, sap replacement and combined method between diffusion and replacement of sap. At the end of the treatments there were removed 1 disk of the base position, middle and top for penetration analysis. At the penetration analysis, disks were sanded on both sides, one for determination of copper with Cromoazurol S and the other for boron with Polyvinyl alcohol and Metallic Iodine with Potassium Iodine, further there were included treatable sapwood measures and treatable sapwood, and the classification of the way it distributes the preservative in different positions of the treated piece. The results showed that the influence of climatic conditions with minimum temperatures presented a high correlation with the first two days of absorption of preservative and inverse correlation with precipitation in relation to preservative absorption. In preservative distribution assessments, the element copper is more efficient on the part of the base position and the element boron in the middle and top positions. The assessments of distribution treatment were satisfactory in the base position for all treatments. In the middle position and the top part of the treatments there were distribution difficulties. In the penetration reviews the results of the base position were satisfactory. The middle position showed low penetration. According to the study results, the methods combined with longer times showed significant improvements in penetration of preservatives in Eucalyptus grandis.